New methods in diagnosis and therapyTransradial approach for carotid artery stenting in a patient with severe peripheral arterial disease - Maciejewski, Damian; Pieniążek, Piotr; Tekieli, Łukasz; Paluszek, Piotr; Dzierwa, Karolina; Trystuła, Mariusz; Wójcik-Pędziwiatr, Magdalena; Podolec, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
We present a case of a 73-year-old man with critical bilateral internal carotid artery stenosis, recent right-hemisphere stroke and severe peripheral artery disease in whom right internal carotid artery stenting (RICA-CAS) was performed successfully via a right transradial approach.